2015
DOI: 10.1038/hdy.2015.91
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive selection and coevolution at the proteins of the Polycomb repressive complexes in Drosophila

Abstract: JM Calvo-Martín, P Librado, M Aguadé, M Papaceit and C Segarra Polycomb group (PcG) proteins are important epigenetic regulatory proteins that modulate the chromatin state through posttranslational histone modifications. These interacting proteins form multimeric complexes that repress gene expression. Thus, PcG proteins are expected to evolve coordinately, which might be reflected in their phylogenetic trees by concordant episodes of positive selection and by a correlation in evolutionary rates. In order to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…The Caf1-55 and Caf1-55dup sequences retrieved from FlyBase were aligned with those reported in Calvo-Martín et al 14. and in the present study.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The Caf1-55 and Caf1-55dup sequences retrieved from FlyBase were aligned with those reported in Calvo-Martín et al 14. and in the present study.…”
Section: Resultssupporting
confidence: 66%
“…This complex contains three additional proteins: E(Z), ESC and SU(Z)12. In a previous study14, it was shown that the genes coding these proteins suffered a significant increase in the nonsynonymous substitution rate in the lineage ancestral to the obscura group species. Therefore, in this lineage not only took place the duplication of Caf1-55 , but also an acceleration in the fixation rate of nonsynonymous changes in the genes encoding proteins that interact with CAF1-55.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These interacting proteins are expected to evolve co-ordinately to maintain the integrity and functionality of the complexes, which can cause a correlation in their evolutionary rates. Evidence of coevolution among the subunits of these complexes has been detected in a previous study of interspecific nucleotide divergence in the Drosophila genus [ 15 ]. Moreover, this study revealed an acceleration in the nonsynonymous substitution rate in the lineage ancestral to the obscura group species, mainly in genes encoding subunits of the Pcl-PRC2 complex.…”
Section: Introductionmentioning
confidence: 95%
“…PRC1 can recognize the H3K27me3 repressive marks set by PRC2 through the chromodomain of Pc gene. In addition to these two PRC complexes, PcG proteins are also present in the three distinct accessory complexes, as follows: the Polycomb repressive deubiquitinase (PR-DUB), dRING-associated factors (dRAF) and Pho repressive complex (PhoRC) complexes (Calvo-Martin et al, 2016). The PR-DUB complex consists of an ubiquitin carboxy-terminal hydrolase, calypso, and an additional sex comb gene, Asx, which encodes a chromatin protein that regulates the balance of Polycomb and Trithorax function.…”
Section: Introductionmentioning
confidence: 99%